ESTIMATING INVESTMENT RETURNS AND RISKS USING THE GARCH MODEL: FOR A SAMPLE OF INDUSTRIAL COMPANIES LISTED IN THE IRAQ STOCK EXCHANGE - AN ANALYTICAL STUDY - Mohammad Ali Abd, (Galaxy International Interdisciplinary Research Journal, 2023)
: The study aims to estimate the relationship between investment returns and risks for a sample of companies listed in the Iraqi Stock Exchange, and aims to study the systemic risks that accompany returns and how to reduce their effects. The study sample is the companies listed in the financial market. The sample of the study may reach (4) industrial companies for a period of five years from 1/1/2017 until 31/12/2021. The Garch statistical model was used to find out the returns and systemic risks depending on the closing prices of the same companies in the study. The importance of the study lies in dealing with an important sector in the Iraqi economy, and this sector is an important link in the Iraqi economy, and knowing the most important factors affecting the return, for the purpose of avoiding them in order to achieve more returns and the causes of systemic risks, and the study reached a set of conclusions, the most important of which is that there is a relationship A direct correlation between return and risk, that is, the greater the investor's ambition to achieve a higher return, the more he must bear the highest risk. The study also noted that some stock prices in the Iraqi stock market are similar for more than a month, due to the low demand for buying corporate shares, and the study recommended the need to ensure The financial reports published by the companies listed on the Iraqi Stock Exchange have information related to expectations of achieving returns in order to assist investors in making sound and rational investment decisions, as well as the continuous study of the published financial information to ensure its accuracy, as it is relied upon in making appropriate investment decisions, and in a manner that ensures achieving the highest returns. The required, and the need to take into account the impact of the relationship between return and risk in building an investment decision in companies It has a great role in achieving returns. Before making any investment decision, the investor should determine the goals he wishes to achieve through the investment process, as well as determine the level of risk that the investor can bear.